2020
DOI: 10.1186/s12957-020-1807-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of limited-stage small cell lung cancer with comprehensive treatment including radical resection

Abstract: Background: The NCCN (National Comprehensive Cancer Network) Clinical Practice Guidelines in Oncology (NCCN guidelines) recommend radical resection for T1-2N0M0 patients with limited-stage small cell lung cancer (LS-SCLC). However, only about 5% of patients with small cell cancer (SCLC) were initially diagnosed as T1-2N0M0. The purpose of our study was to analyze and compare the effects of the comprehensive treatment including radical surgery and concurrent chemoradiotherapy on the prognosis of patients with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 22 publications
0
29
1
Order By: Relevance
“…4d, Table 2, univariate survival analysis P = 0.019, multivariate analysis P = 0.014). Zhong et al [34] reported that preoperative neoadjuvant radiochemotherapy did not improve the prognosis of patients who were surgically treated for SCLC, and our study did not nd any prognostic bene t of neoadjuvant therapy (P = 0.39). However, because this study is a retrospective study with a long time span, the chemotherapy and radiotherapy regimens and the implementation standards of neoadjuvant therapy for patients were inconsistent throughout the study period.…”
Section: Survival Analysiscontrasting
confidence: 47%
“…4d, Table 2, univariate survival analysis P = 0.019, multivariate analysis P = 0.014). Zhong et al [34] reported that preoperative neoadjuvant radiochemotherapy did not improve the prognosis of patients who were surgically treated for SCLC, and our study did not nd any prognostic bene t of neoadjuvant therapy (P = 0.39). However, because this study is a retrospective study with a long time span, the chemotherapy and radiotherapy regimens and the implementation standards of neoadjuvant therapy for patients were inconsistent throughout the study period.…”
Section: Survival Analysiscontrasting
confidence: 47%
“…These are the main reasons why smoking affects postoperative complications (22)(23)(24). Some studies have shown that neoadjuvant chemotherapy combined with surgery can improve the prognosis of SCLC patients, as neoadjuvant chemotherapy may reduce the T or N stage of the tumor, thereby reducing the risk of death (25)(26)(27). Among patients with nodal metastases, only those with negative nodes following induction chemo/ chemoradiotherapy should be candidates for surgery (15).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the homogeneous platinum based systemic chemotherapy approach in ES-SCLC, LS-SCLC is treated with varied treatment modalities based on clinical characteristics such as the lung function and TNM stage. Recently, surgical resection and concurrent chemoradiotherapy are recommended for LS-SCLC with T1-2N0M0 [35]. Moreover, the study for the radiotherapy schedule, radiation dose, and the candidate for prophylactic cranial irradiation has been continuously conducted to improve the prognosis of patients with LS-SCLC [36, 37].…”
Section: Discussionmentioning
confidence: 99%